A new species of Joguina Navás, 1912 from India (Neuroptera: Chrysopidae) - Winterton, Shaun L.; Balakrishnan, Suryanarayanan Thangalazhi; Chenthamarakshan, Bijoy (Zootaxa, 2021)
A new species of the delicate lacewing, Joguina Navás, 1912 (Chrysopidae: Apochrysinae) is described and figured from south-western India. A key to species of Joguina is presented as well as revised diagnoses of both Joguina and its sister genus, Lainius Navás, 1913 stat. rev.